Does financial development reduce poverty? Empirical evidence from Indonesia - Abd. Majid, M. Shabri; ,, Sovia Dewi; ,, Aliasuddin; Kassim, Salina (Springer, 2019)
This paper contributes to the literature by providing empirical evidence on the relationship between financial development, economic growth, and poverty in Indonesia in the period of 1980–2014. This issue is of importance for developing economies such as Indonesia given the high rate of poverty in the country despite the rapid growth of the financial sector. The Autoregressive distributed lag (ARDL) approach to cointegration is used to examine the long-run relationship between the financial sector development and poverty, while the Granger causality based on the VECM approach is used to ascertain the direction of the causal relationship between the variables. In arriving at robust findings, we investigated two models, each using different indicators of financial sector growth, namely money supply (M2), and ratio of domestic credit to private sector to gross domestic product. The study finds that there was a long-run relationship between the financial sector, economic growth, and poverty in Indonesia, while in the short run, a bi-directional causal relationship exists between the financial sector and poverty. Based on these findings, it is recommended that in efforts to reduce poverty, the government should focus on facilitating the channelling of funds from the financial sector into specific segment of the population to ensure fair accessibility of credit, especially to the low-income group in Indonesia.